Achieving IT‐based synergies through regulation‐oriented and consensus‐oriented IT governance capabilities. (3rd November 2017) - Kude, Thomas; Lazic, Miroslav; Heinzl, Armin; Neff, Alexander
Abstract: This study aims at exploring the IT governance capabilities that enable organizations to achieve IT‐based synergies. Following existing work on the contextualization of theories and drawing on the resource‐based view of the firm (RBV), we develop an RBV of IT‐based synergies in two steps. First, we adopt existing context‐specific constructs and relationships from prior work on IT governance capabilities, IT relatedness, and synergies to develop a preliminary contextualization of the RBV. Second, to further refine our theoretical framework, we conduct an exploratory field study that includes interviews with 26 CIOs and other IT executives from 21 multibusiness firms. Our findings suggest that IT governance capabilities lead to IT‐based synergies through IT relatedness and business process relatedness. We found regulation‐oriented IT governance capabilities (IT roles and IT processes) to increase IT relatedness, while consensus‐oriented IT governance capabilities (IT groups and relational capabilities) had a positive effect on business process relatedness. Our results suggest that, in isolation, IT and business process relatedness lead to IT cost synergies, while collectively enabling IT‐induced business synergies. Our study is among the first to treat IT relatedness as an endogenous construct and to explicitly integrate business process relatedness into the IT governance domain. Our context‐specific decomposition of IT governance capabilities helps to better explain their links to IT and business process relatedness. These findings contribute to a better understanding of the tension between IT‐based synergies and business‐IT alignment. Decision‐makers are guided in developing IT governance capabilities to achieve IT‐based synergies.